Os ambulantes no carnatal: oportunidades de trabalho ou lazer? - Savall, Elaine Cristina Alves da Costa; Cavignac, Julie Antoinette (Revista Inter-Legere, 2013)
Os ambulantes no carnatal: oportunidades de trabalho ou lazer?